2010
DOI: 10.1177/1938640010374981
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Extreme Ankle Range of Motion Required by Female Ballet Dancers

Abstract: Female ballet dancers require extreme ankle motion, especially plantar flexion, but research about measuring such motion is lacking. The purposes of this study were to determine in a sample of ballet dancers whether non-weight-bearing ankle range of motion is significantly different from the weight-bearing equivalent and whether inclinometric plantar flexion measurement is a suitable substitute for standard plantar flexion goniometry. Fifteen female ballet dancers (5 university, 5 vocational, and 5 professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 23 publications
6
42
2
2
Order By: Relevance
“…Greater mid-foot flexion in the worn pointe shoe appears to result from the metatarsals curling underneath the foot whilst en pointe (Russell, 2015), which may cause excessive stretching of the ligaments, which connect the metatarsal bones. This was accompanied by high levels of plantarflexion, comparable to those previously reported (173 degrees, Russell et al, 2010b). In this position, the anterior talofibular ligament acts as the primary stabilizer of the lateral ankle, which places it at risk of injury due to high tensile forces and unfavorable strain length (Cawley & France, 1991;Bahr, Pena, Shine, Lew, & Engebretsen, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…Greater mid-foot flexion in the worn pointe shoe appears to result from the metatarsals curling underneath the foot whilst en pointe (Russell, 2015), which may cause excessive stretching of the ligaments, which connect the metatarsal bones. This was accompanied by high levels of plantarflexion, comparable to those previously reported (173 degrees, Russell et al, 2010b). In this position, the anterior talofibular ligament acts as the primary stabilizer of the lateral ankle, which places it at risk of injury due to high tensile forces and unfavorable strain length (Cawley & France, 1991;Bahr, Pena, Shine, Lew, & Engebretsen, 1998).…”
Section: Discussionsupporting
confidence: 84%
“…Ballet dancing en pointe requires absolutely maximum plantar flexion in order to attain the position required to maintain the esthetics of the art form (1). This position is sufficiently severe and prone to injury that guidelines are in place to assist dancers, dance teachers, parents, and healthcare professionals with the process of properly introducing girls to this form of dance (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the plantar flexion of the ankle joint showed that in 13 cases of injured limbs (86.7%) we had values below the normal range and in 12 cases (80%) of uninjured limbs, we also had values below the normal range. The full range of motion in plantar flexion ranges from 45° -50°, although in professional ballet dancers values above the full and normal range of motion have been observed (Russell, Kruse, Nevill, Koutedakis & Wyon, 2010). This is due to the continuous effort made by professional ballet dancers to improve the range of plantar flexion in order to meet the requirements of their activity (Hamilton, Hamilton, Marshall & Molnar, 1992).…”
Section: Discussionmentioning
confidence: 99%